Coordination behaviour of 2-(Methylthio)Pyrazine with Ag(I) in the presence of different counter anions and emission properties. (1st September 2019) - Singh, Suryabhan; Raghuvanshi, Abhinav; Mathur, Pradeep; Singh, Amrendra K.
Graphical abstract: Three new Ag-MTP coordination polymers have been synthesized in the presence of PF6, NO3 and OTf anions. The single crystal X-ray study reveals that CPs1 and2 are two dimensional, whereas3 is three dimensional. The emission behaviour of CPs in the presence of different metal ions confirms that only CP1 has affinity towards Hg(II) and Cu(II) ions. Abstract: Three new coordination polymers (CPs), [Ag(MTP)2 (PF6 )] n 1, [Ag(MTP)(NO3 )] n 2 and [Ag(MTP)(OTf)] n 3 (where MTP = 2-(Methylthio)Pyrazine and OTf = CF3 SO3 − ) have been synthesized and characterized by different spectroscopic techniques. The single crystal X-ray study reveals that CPs1 and2 are two dimensional, whereas3 is three dimensional. In the case of CP1, MTP has two types of bonding behaviour. In one it is coordinated through the nitrogen of pyrazine only, leaving sulfur of –SMe free, whereas, in the other, it bonded through both sulfur and nitrogen of MTP. The sulfur of –SMe is coordinated to the neighbouring [Ag(MTP)] n chain in2 whereas, in case of3, sulfur of –SMe remain uncoordinated. Absorption and emission spectra of MTP and CPs have been studied in solution state. The spectral behaviour was supported by time dependent density functional theory. The emission behaviour of CPs in the presence of different metal ions confirms that only CP1 has some affinity towards Hg(II) and Cu(II) ions.